Introduction to Mass Communication : Media Literacy and Culture - Stanley J. Baran (Mc Graw Hill, 2006)
Berisi : Media Tours Video Tracks 1-5, Video Transcripts, Learning Styles Assessment, PowerPoint Tutorial, Guide to Electronic Research, A link to the online Learning Center ; CD 2 berisi : Media Tours Video Track 6, NBC Video Clips, Video Transcripts, Self-Quizzes, Media Literacy Worksheets, A link to the Online Learning Center.